1997
DOI: 10.1021/ie970283c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of Multiple Steady States in Heterogeneous Azeotropic Distillation

Abstract: An experimental study of ethanol dehydration with cyclohexane as the entrainer has been carried out in order to verify the existence of multiple steady states in heterogeneous azeotropic distillation. As a basis, the bifurcation diagram for the ethanol product purity is determined from thermodynamic considerations using the distillate flow rate as the bifurcation parameter. The predicted multiple steady states are then verified by rigorous simulation and by experiments on a laboratory tray column with a decant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Thus, for single-feed distillation columns with a distillate and bottom product only one parameter remains, e.g., the distillate-tofeed ratio D/F. The application of ∞/∞ -analysis to heterogeneous systems is straightforward Müller and Marquardt, 1997;Müller, 1998), if the respective vapor-liquid equilibrium diagram has been generated by considering the liquid phase-split (Kiva et al, 2003;Królikowski et al, 2011).…”
Section: Application To Heterogeneous Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for single-feed distillation columns with a distillate and bottom product only one parameter remains, e.g., the distillate-tofeed ratio D/F. The application of ∞/∞ -analysis to heterogeneous systems is straightforward Müller and Marquardt, 1997;Müller, 1998), if the respective vapor-liquid equilibrium diagram has been generated by considering the liquid phase-split (Kiva et al, 2003;Królikowski et al, 2011).…”
Section: Application To Heterogeneous Systemsmentioning
confidence: 99%
“…∞/∞ -Analysis supports various tasks in conceptual design like feasibility, multiplicity studies, and bifurcation analysis (Bekiaris et al, 1993. Therefore, it has been systematically used for studying homogeneous and heterogeneous azeotropic distillation (Bekiaris et al, 1993;Müller and Marquardt, 1997;Müller, 1998). Further, it has successfully been applied to processes with more than one unit operation in a flow sheet (see e.g., Laroche et al, 1992;Esbjerg et al, 1998;Güttinger and Morari, 1996;Blagov et al, 2000;Nazanskii et al, 2001;Ulrich, 2002;Ulrich and Morari, 2003;Bonet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bossen et al (1993) found four steady states for the dehydration of ethanol with benzene by dynamic simulation. Moreover, by means of a dynamic experiment, Müller and Marquardt (1997) verifi ed both the existence of multiple steady states in a heterogeneous azeotropic distillation (ethanol dehydration with cyclohexane as entrainer) and the hysteresis behaviour due to multiple steady states. On the other hand, Chien et al (1999) analysed the dynamic behaviour of another heterogeneous azeotropic column (isopropyl alcohol-cyclohexane-water).…”
mentioning
confidence: 93%
“…The routines developed for computing steady state are sensitive to initial estimates, and if no solution is achieved after several attempts with different initial points then one does not know whether the initial estimation is bad or simply that no solution exists for the specified circumstances. Moreover, there are specifications that give rise to several solutions (output multiplicity 14,15 ).…”
Section: Introductionmentioning
confidence: 99%